2005
DOI: 10.1016/j.cell.2005.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Dynamic Assessment of the Contribution of the ER to Phagosome Formation

Abstract: Phagosomes were traditionally thought to originate from an invagination and scission of the plasma membrane to form a distinct intracellular vacuole. An alternative model implicating the endoplasmic reticulum (ER) as a major component of nascent and maturing phagosomes was recently proposed (Gagnon et al., 2002). To reconcile these seemingly disparate hypotheses, we used a combination of biochemical, fluorescence imaging, and electron microscopy techniques to quantitatively and dynamically assess the contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
209
1
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 252 publications
(223 citation statements)
references
References 59 publications
10
209
1
3
Order By: Relevance
“…Confocal microscopy has shown that internal membranes within the cell fuse with plasma membrane during the course of particle ingestion, and that recycling endosomes are the primary source of membrane for enlargement of phagocytic cup [22]. Flow cytometric assessment of particle engulfment has to some extent replaced microscopic observation [23] particularly as the kinetics of uptake of fluorescent targets by phagocytes can be followed by instruments capable of time-resolved measurements in a stirred cuvette at 37°C [24].…”
Section: Flow Cytometric Assay Of Phagocytosismentioning
confidence: 99%
“…Confocal microscopy has shown that internal membranes within the cell fuse with plasma membrane during the course of particle ingestion, and that recycling endosomes are the primary source of membrane for enlargement of phagocytic cup [22]. Flow cytometric assessment of particle engulfment has to some extent replaced microscopic observation [23] particularly as the kinetics of uptake of fluorescent targets by phagocytes can be followed by instruments capable of time-resolved measurements in a stirred cuvette at 37°C [24].…”
Section: Flow Cytometric Assay Of Phagocytosismentioning
confidence: 99%
“…Other studies suggested the existence of endoplasmic reticulum (ER)-mediated phagocytosis (8 -10), whereby the ER membrane was targeted to the phagocytic site to aid in phagosome formation. However, by using a combination of biochemical, fluorescence imaging and electron microscopy techniques, Grinstein and colleagues (11) did not obtain evidence to prove the direct fusion between the ER and the plasma membrane. ER-mediated phagocytosis remains a subject of controversy.…”
Section: Vesicle-associated Membrane Protein-8/endobrevin Negativelymentioning
confidence: 99%
“…Mais la majeure partie de l'attention portée à ce modèle était due à sa capacité d'expliquer le mécanisme mal compris de la présentation croisée des antigènes [4,5]. La participation du RE dans la formation du phagosome a été récemment ré-examinée en utilisant diverses approches biophysiques et biochimiques [6]. Une quantification des composants du phagosome présents au cours de sa formation par microscopie de fluorescence ou électronique, et par une approche biochimique intégrative, n'a indiqué aucune contribution significative du RE.…”
unclassified